Correlation between power harrow energy demand and tilled soil aggregate dimensions. (January 2023) - Varani, Massimiliano; Mattetti, Michele; Molari, Giovanni; Biglia, Alessandro; Comba, Lorenzo
Abstract : Energy demand of soil tillage implements has been reported based on different operating conditions and the chemical and physical soil properties. However, tillage operations cannot only be evaluated according to their energy consumption; the soil structure improvement and the consequent agronomic benefits must also be considered. Power harrows can adjust soil clod size by varying the velocity ratio (λ) of the machinery which is calculated from the ratio of the peripheral speed of the tine rotors and the vehicle's advancing speed. This paper aims to gain deeper insight into controlling the soil structure and find correlations with the power harrow's energy requirement in different setups. Field tests were conducted at the experimental farm of the University of Bologna on a 3-m working width power harrow coupled with a tractor with 107 kW of rated engine power. Field tests were performed by varying λ from 1.46 to 7.90 while tractor parameters, such as speed, engine power, fuel rate consumption, draught, and power take-off (PTO) speed and torque, were acquired with a datalogger. After harrowing, soil samples were sieved and significant granulometric parameters were calculated and correlated to data acquired from the tractor–power harrow system. The results show that the optimum conditions for a high-quality seedbed are obtained with high values of implement–soil impact speed, whilst λ should be kept as low as possible to minimise the fuel consumption per ha. Highlights: Efficiency and seedbed quality must be considered during tillage operation. A 25% efficiency improvement was obtained at high power harrow absorbed power. High implement–soil impact speeds reduce the soil aggregate size.